Elucidation of Vasodilation Response and Structure Activity Relationships of N2,N4-Disubstituted Quinazoline 2,4-Diamines in a Rat Pulmonary Artery Model - Tamkeen Urooj Paracha; Nattakarn Pobsuk; Nattapas Salaloy; Praphasri Suphakun; Dumrongsak Pekthong; Supa Hannongbua; Kiattawee Choowongkomon; Nantaka Khorana; Prapapan Temkitthawon; Kornkanok Ingkaninan; M. Paul Gleeson; Krongkarn Chootip (My University, 2019)
Pulmonary arterial hypertension (PAH) is a rare and progressive disease arising from various etiologies and pathogenesis. PAH decreases life expectancy due to pulmonary vascular remodeling, elevation of mean pulmonary arterial pressure, and ultimately progresses to heart failure. While clinical treatments are available to reduce the associated symptoms, a complete cure has yet to be found. Phosphodiesterase-5 (PDE-5) inhibition has been identified as a possible intervention point in PAH treatment. The functional vasodilation response to N²,N⁴-diamino quinazoline analogues with differing PDE-5 inhibitory activities and varying physicochemical properties were assessed in both endothelium-intact and denuded rat pulmonary arteries to gain greater insight into their mode of action. All analogues produced vasorelaxant effects with EC50s ranging from 0.58 ± 0.22 µM to ˃30 µM. It was observed that vasodilation response in intact vessels was highly correlated with that of denuded vessels. The ~10% drop in activity is consistent with a loss of the nitric oxide mediated cyclic guanosine monophosphate (NO/cGMP) pathway in the latter case. A moderate correlation between the vasodilation response and PDE-5 inhibitory activity in the intact vessels was observed. Experimental protocol using the alpha-adrenergic (α₁) receptor agonist, phenylephrine (PE), was undertaken to assess whether quinazoline derivatives showed competitive behavior similar to the α₁ receptor blocker, prazosin, itself a quinazoline derivative, or to the PDE-5 inhibitor, sildenafil. Competitive experiments with the α₁-adrenergic receptor agonist point to quinazoline derivatives under investigation here act via PDE-5 inhibition and not the former. The pre-incubation of pulmonary arterial rings with quinazoline test compounds (10 μM) reduced the contractile response to PE around 40⁻60%. The most promising compound (9) possessed ~32 folds higher selectivity in terms of vasodilation to its mammalian A549 cell cytotoxicity. This study provides experi0 0mental basis for PDE-5 inhibition as the mode of action for vasodilation by N²,N⁴-diamino quinazoline analogues along with their safety studies that may be beneficial in the treatment of various cardiovascular pathologies.
Keywords: Phenylephrine; Cyclic guanosine monophosphate; Soluble guanylyl cyclase; Pulmonary Hypertension Research and Treatments